Attachment and emotional development in the classroom : theory and practice - Geddes, Heather; Nash, Poppy; Cahill, Janice; Satchwell-Hirst, Maisie; Thierry, Betsy de; Wilson, Peter; Rose, Janet; Colley, David; Cooper, Paul, 1955-; Carpenter, Barry (Jessica Kingsley Publishers, 2017)
As part of preparation for the classroom, it's key for trainee teachers to understand the emotional needs of students. This book provides a clear introduction to emotional development and attachment, offering advice and guidance from a diverse range of professional perspectives including psychology, health and education.